2016
DOI: 10.1111/jfb.13200
|View full text |Cite
|
Sign up to set email alerts
|

Plasma osmolality and oxygen consumption of perch Perca fluviatilis in response to different salinities and temperatures

Abstract: The present study determined the blood plasma osmolality and oxygen consumption of the perch Perca fluviatilis at different salinities (0, 10 and 15) and temperatures (5, 10 and 20° C). Blood plasma osmolality increased with salinity at all temperatures. Standard metabolic rate (SMR) increased with salinity at 10 and 20° C. Maximum metabolic rate (MMR) and aerobic scope was lowest at salinity of 15 at 5° C, yet at 20° C, they were lowest at a salinity of 0. A cost of osmoregulation (SMR at a salinity of 0 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 54 publications
(74 reference statements)
1
17
0
1
Order By: Relevance
“…Perca flavescens also have anadromous ancestry (Victoria et al, ), which could enable them to cope readily with salinity changes within their limited tolerance. The results are in accordance with a study on the P. fluviatilis , a closely related sister species to P. flavescens (Stepien et al, ), which showed a significantly decreased aerobic scope in fresh water, compared with a salinity of 10 (Christensen et al, ). The reduced aerobic scope observed in freshwater acclimated P. fluviatilis suggested elevated metabolic demands associated with osmoregulation.…”
Section: Mean ± Sd Per Cent Residence Time Over a Period Of 18–20 Hsupporting
confidence: 92%
“…Perca flavescens also have anadromous ancestry (Victoria et al, ), which could enable them to cope readily with salinity changes within their limited tolerance. The results are in accordance with a study on the P. fluviatilis , a closely related sister species to P. flavescens (Stepien et al, ), which showed a significantly decreased aerobic scope in fresh water, compared with a salinity of 10 (Christensen et al, ). The reduced aerobic scope observed in freshwater acclimated P. fluviatilis suggested elevated metabolic demands associated with osmoregulation.…”
Section: Mean ± Sd Per Cent Residence Time Over a Period Of 18–20 Hsupporting
confidence: 92%
“…After the U crit and respirometry trial, the fish was directly transferred to a custom-made, cylindrical, acrylic static respirometer of 1.430 L, set up as in [54]. Here,ṀO 2 was measured over a period of 22-24 h with a fiber optic oxygen sensor (Firesting Pro 1 channel, PyroScience GmbH, Aachen, Germany) by automated intermittent-flow respirometry [53], allowing for estimation of SMR [33].…”
Section: Methodsmentioning
confidence: 99%
“…The other distribution represented spontaneous activity, which was thus excluded from the SMR determination. MMR from the static respirometry trial was defined as the highest measuredṀO 2 [54]. Aerobic scope from the static respirometry was calculated at the difference between MMR and SMR during the trial.…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
“…The fact that the respiratory response observed on rainbow trout corresponds to that of gill irritants using the FATS approach [20] suggests that the toxin is not likely to have any direct action on the inner physiology of the fish. Lastly, both the damaged gill epithelia, in connection with the increased ventilatory volume, will provide the fish with a severe osmotic challenge [63]. This osmotic challenge and its associated costs to the fish remains undetermined.…”
Section: Discussionmentioning
confidence: 99%